PENINGKATAN KEKUATAN TARIK SAMBUNGAN SINGLE V-GROOVE BAJA ST37 DENGAN VARIASI ARUS PENGELASAN SMAW - Alief Muhammad; Dani Hari Tunggal Prasetiyo; Akbar Anugrah Ikhsani; Setyo Pambudi (ROTOR, 2021)
Welding and casting processes have become an important focus in the development of industry 5.0. In improving welding efficiency, increasing the number of tests on many variables is the first step in optimizing production. Welding optimization aims to find the best solution and result in a production process, it takes a lot of welding experimental data to be able to compare it. The Shielded Metal Arc Welding (SMAW) is becoming very common in all industries. SMAW has several variables that can affect welding results, one of which is the electric current used. This study aims as an effort in the current industrial development is to present data on the effect of SMAW welding electric current on its tensile strength for optimization. In this study, the mechanical strength tested was tensile strength and current susceptibility used was 80 to 140 Ampere commonly used using ST-37 Steel. The highest maximum loading value occurred in the sample with a current of 80 A of 72.78 kN. However, the highest maximum stress, fracture, and yield occurred in the sample with a current of 140 A of 734.66; 594.28; 558.29 MPa.